2015
DOI: 10.1088/0031-8949/90/4/045502
|View full text |Cite
|
Sign up to set email alerts
|

EIT enhanced self-Kerr nonlinearity in the three-level lambda system under Doppler broadening

Abstract: Using density-matrix theory, an analytical expression of the self-Kerr nonlinear coefficient of a three-level lambda EIT medium for a weak probe light is derived. Influences of the coupling light and Doppler broadening on the self-Kerr coefficient are investigated and compared to experimental observation with a good agreement. The self-Kerr nonlinearity of the medium is modified and greatly enhanced in the spectral region of EIT window. Furthermore, sign, slope, and magnitude of the self-Kerr coefficient can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…The measurement shows a great enhancement of the Kerr nonlinear index of refraction in several orders of magnitude around atomic resonance [12]. Recently, Doai et al [13] have developed an analytical model of EIT enhanced self-Kerr nonlinearity with controllable parameters of a light field and temperature of atomic sample which is in good agreement with the experimental observations [12]. The studies showed that the Kerr nonlinearity2 International Journal of Optics bistability in the three-level EIT system inside an optical ring cavity in the presence of Doppler broadening.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The measurement shows a great enhancement of the Kerr nonlinear index of refraction in several orders of magnitude around atomic resonance [12]. Recently, Doai et al [13] have developed an analytical model of EIT enhanced self-Kerr nonlinearity with controllable parameters of a light field and temperature of atomic sample which is in good agreement with the experimental observations [12]. The studies showed that the Kerr nonlinearity2 International Journal of Optics bistability in the three-level EIT system inside an optical ring cavity in the presence of Doppler broadening.…”
Section: Introductionmentioning
confidence: 84%
“…The self-Kerr coefficient 2 can be determined by using the density matrix formalism. Under the framework of the semiclassical theory and dipole and rotating wave approximations, the evolution of the three-level system can be represented by [13] …”
Section: The Mater Equation Of Obmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was proposed theoretically in 1989 [1] and experimentally verified in 1991 [2]. Since then, the EIT has attracted much studies in atomic/molecular systems [3][4][5][6][7][8][9][10][11][12][13][14] and quantum well/dot systems [15][16][17][18][19] due to its unusual optical properties and promises for potential applications, such as lasing without inversion [20], high resolution spectroscopy [21], nonlinear optics at low light levels [22], giant Kerr nonlinearity [23][24][25][26], and optical bistability (OB) [27]. In addition to the reduction of the resonant absorption, modification of refractive index of the EIT medium was also studied theoretically [28,29] and experimentally [8,30].…”
Section: Introductionmentioning
confidence: 99%
“…The EIT effect was proposed theoretically in 1989 [1] and experimentally verified in 1991 [2]. Since then, the EIT effect has attracted a tremendous interest over the last years due to its unusual properties and promising potential applications, e.g., laser without inversion [3], slow-light [4], enhancement of Kerr nonlinearity [5,6], and so on. In addition to applications from the point of view of the atomic system and its optical response, pulse propagation under EIT conditions has also been widely studied, such as: propagation of soliton-like pulses in a three-level system [7], pulse propagation in a prepared energy medium [8], adiabatic propagation of short laser pulses [9], dynamical control of pulse propagation [10][11][12][13][14], etc.…”
mentioning
confidence: 99%